Development of Ethnomathematics-Based Test Instrument to Measure Critical Thinking Ability - Munawarah, Munawarah; Novianty, Rina; Nur, Fitriani; Mattoliang, Lisnasari Andi; Thalhah, Sitti Zuhaerah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
In an effort to improve one's critical thinking skills through mathematics, of course, an instrument or special material is needed to measure critical thinking skills, one of which is through an ethnomathematics-based test instrument. This research is research and development (R&D), which involves developing test instruments with the formative research model (Tessmer). This development goes through two stages, namely preliminary and self-evaluation stages. The research was conducted on 4th-semester students who had studied mathematical economics. Validation sheets, tests, and questionnaires were used to collect data. The data collected were analysed using question validity analysis, student and lecturer response analysis, and test quality analysis, including reliability, difficulty level, and differentiability. At the same time, the critical thinking skills of students will be analysed descriptively. The results of this development obtained ethnomathematics-based test instruments that meet the criteria for validity, reliability, differentiability, difficulty level, and practicality according to standards. Thus, ethnomathematics-based test instruments are feasible to use to measure students' critical thinking skills.